Rekontruksi Manual Book Berbasis Etnosains tentang Kadar Sianida dan Kandungan Nutrisi Lemea Terintegrasi Bioteknologi untuk Meningkatkan Keterampilan Proses Siswa SMP - Roleka Julia Marcellina; Bhakti Karyadi; Rendy Wikrama Wardana; Euis Nursa’adah; Afrizal Mayub (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to develop an ethnoscience-based guidebook by integrating lemea fermentation as a local context in biotechnology learning to improve junior high school students' science process skills. The development model used is ADDIE with a quasi-experimental design of non-equivalent control groups. The research subjects consisted of 48 ninth-grade students from SMPN 02 Lebong, divided into experimental and control groups. Research instruments included observation, expert validation, pretest, posttest, and questionnaires. Validation results indicated product feasibility of 92% (very feasible category). Effectiveness testing using an independent t-test showed a significant difference between the experimental and control groups (Sig. 0.000 < 0.05), with an average N-Gain of 0.43 (moderate) in the experimental group and 0.17 (low) in the control group. The effect of media use on science process skills was moderate. Student and teacher responses to the media were very positive, particularly in terms of appearance, content, and usefulness. These results indicate that the integration of local culture into science is effective in developing students' scientific skills in a contextual manner.